Effect of hydrogen on evolution of deformation microstructure in low-carbon steel with ferrite microstructure. (15th February 2022) - Okada, Kazuho; Shibata, Akinobu; Gong, Wu; Tsuji, Nobuhiro
Abstract: In this study, the deformation microstructure of hydrogen-charged ferritic-pearlitic 2Mn-0.1C steel was characterized using SEM-BSE, SEM-EBSD, TEM, and neutron diffraction. The microscopic mechanism of hydrogen-related quasi-cleavage fracture along the {011} planes was also discussed. It was found that hydrogen increased the relative velocity of screw dislocations to edge dislocations, leading to a tangled dislocation morphology, even at the initial stage of deformation ( e  = 3%). In addition, the density of screw dislocations at the later stage of deformation ( e  = 20%) increased in the presence of hydrogen. Based on the experimental results, it is proposed that a high density of vacancies accumulated along {011} slip planes by jog-dragging of screw dislocations, and coalescence of the accumulated vacancies led to the hydrogen-related quasi-cleavage fracture along the {011} slip planes.